Restarting plastic surgery; drawing on the experience of the initial COVID-19 pandemic to inform the safe resumption of services (2020)
COVID-19 has caused an unprecedented demand on healthcare resources globally. In light of the arrival of a novel contagious and life-threatening virus, the NHS has responded by making difficult decisions to maintain care for patients and protect staff. The response has been frequently amended following updates in UK Government policy as scientific understanding of the virus has improved. Our Plastic Surgery practice has adapted to mitigate risk to patients by reducing face-to-face contact, downgrading emergency procedures and deferring elective surgery where possible. This has inevitably resulted in a backlog in elective surgery and outpatient appointments. An assessment of the long-term health, social and economic impact of NHS wide service reconfiguration upon patient outcomes is yet to be seen. In this paper, we review the demonstrable early effects of service changes upon our unit and compare those to national and internationally published data. We also outline some of the considerations being made as we consider strategies to resume services in the light of the ongoing COVID-19 pandemic.